The Role of Islamic Economics in the Global Economy - Anisa Fitriani; Jamilah; Nadila (Al-Fadilah: Islamic Economics Journal, 2024)
This article explains the role of Islamic economics in the global economy consisting of an introduction, understanding sharia economics, principles of Islamic economics, globalization and the role of Islamic economics in the global economy. This journal is to find out the role of Islamic economics in the global economy in accordance with Islamic economic principles. Islamic economics is based on sharia principles which prohibit usury (interest), gharar (uncertainty), and encourage fair and transparent transactions. These principles support economic stability and social justice. This research concludes that Islamic Economics plays a very important role in the global economy by offering an ethical and sustainable alternative. With the continued development of Islamic finance and increased global awareness of sharia principles, Islamic economics has the potential to make a significant contribution to global economic stability and inclusiveness.